Analisa Perhitungan Pajak Penghasilan Pasal 21, Sebagai Perencanaan Pajak Penghasilan Badan Kantor Jasa Akuntan Surabaya - Lusy; Jessica Fernanda (STIE PGRI Dewantara Jombang, 2022)
In Indonesia, tax are still the biggest contributor to state revenues. There are various types of tax that can be used as a source of state income, one of which is directly related to employees is income tax section 21. The purpose of this study is to analyze the calculation of income tax section 21 with 3 methods (Net, Gross, and Gross Up), as an effort to plan Corporate Income Tax at the Accountant Services Office in Surabaya. The research object used is located in the city of Surabaya and is engaged in service such as bookkeeping service, tax services, financial consulting services, etc. The research method used in this study uses a qualitative approach and supported by quantitative data. The data used is 2017 income list of permanent employees, calculation PPh section 21 by company, and PPh regulation. The conclusion of this research is Gross Up method is the best and effective to be used as Corporate Tax Planning. Because with this Gross Up method, the company provides tax benefits to employees and can be used as a deduction from the company’s gross income so that the paid Corporate Income Tax becomes smaller.